كثافة خلايا البطانة القرنية وشكلها عند الأصحاء في سوريا - درويش, تيم (Latakia University Journal -Medical Sciences Series, 2019)
الهدف: دراسة كثافة خلايا البطانة القرنية وشكلها عند الأصحاء في سوريا و مقارنة خصائص خلايا بطانة القرنية عند المجتمع السوري مع القيم المذكورة للمجتمعات الأخرى. الطرق: تم إجراء فحص بطانة القرنية بالمجهر المرآوي ل 1400 عين (700 مواطن سوري ) العمر بين 18-84سنة. تمت دراسة المعايير التالية متوسط كثافة الخلايا , وسطي مساحة الخلية , معامل تغير حجم الخلايا , نسبة الخلايا السداسية. النتائج: كان متوسط كثافة الخلايا 2664±407 خلية/ملم². نسبة الخلايا السداسية كانت % 8±56 . كان هناك نقص هام احصائيا بكثافة خلايا البطانة و نسبة الخلايا السداسية مع العمر. كان متوسط مساحة الخلية و معامل تغير حجم الخلايا 387 ± 65 µm² و 34±7 على التوالي. كان هناك زيادة ملحوظة بمساحة الخلية و معامل تغير حجم الخلايا مع العمر. لم يكن هناك فرق هام احصائيا بالمعايير السابقة بين الجنسين. الاستنتاج: تم تسجيل القيم الطبيعية لطبقة خلايا البطانة القرنية لدى الأصحاء في سوريا. هذه المعلومات أضافت للمعرفة حول خصائص الخلايا البطانية القرنية في العيون السليمة للأفراد في سوريا و يمكن استخدامها عند المقارنة بالمجتمعات الأخرى. Purpose: To study corneal endothelial cell density and morphology in healthy Syrian eyes and compare endothelial cell characteristics in the Syrian population with data available in the literature for other populations . Methods: Specular microscopy was performed in 1400 eyes of 700 healthy Syrian volunteers , 18 to 84 years of age. Parameters studied included endothelial cell density (CD), cell area (CA), coefficient of variation (CV) in cell area, and percent of hexagonality. Results: Mean endothelial CD in the study population was 2664±407 cells/mm². Percentage of hexagonal cells was 56± 8%. There was a statistically significant decrease in endothelial CD and percentage of hexagonal cells with age. Mean CA, and CV, were 387 ± 65 µm², and 34±7 respectively. There was also a statistically significant increase in CA and CV with increasing age. There was no statistically significant difference in MCD, MCA, CV and percent hexagonality between genders. Conclusions: Normative data for the corneal endothelium in the Syrian population are reported. Our data add to the knowledge about endothelial cell parameters in Syrian eyes and serve as a baseline for comparative studies with other populations.